S25 Enhanced detection of non-tuberculous mycobacteria (NTM) in patients with bronchiectasis using RGM medium compared to conventional AFB culture. (December 2018) - Stephenson, D; Perry, A; Appleby, MR; Davison, J; Jones, AL; Nelson, A; Lumb, J; Walton, KE; De Soyza, A; Perry, JD
Abstract : Introduction and objectives: Non-tuberculous mycobacteria (NTM) are significant respiratory pathogens that have been estimated to affect around 9% of individuals with non-cystic fibrosis bronchiectasis (BR). Detection of NTM is achieved by conventional culture for acid-fast bacilli (AFB) following chemical decontamination of sputum samples. Such decontamination is known to reduce the viability of NTM thus compromising the sensitivity of detection. A novel culture medium, RGM medium, allows culture of NTM without decontamination of samples, potentially increasing sensitivity of detection. We compared culture of respiratory samples on RGM medium with conventional AFB culture for 266 samples from 204 individuals with BR. Methods: All samples were subjected to conventional AFB culture for up to 56 days using national standard methods. This involved decontamination of samples with sodium hydroxide followed by inoculation of a Mycobacterial Growth Indicator Tube (MGIT) plus Löwenstein-Jensen medium with incubation for up to 56 days. In parallel, samples were inoculated directly onto RGM medium (without decontamination) with incubation for 28 days at 30°C. NTM were identified using standard methods. Results: 114 isolates of NTM were recovered using a combination of both methods. 112 were isolated on RGM medium compared with 14 using conventional AFB culture (sensitivity: 98% versus 12%, p<0.0001). For Mycobacterium avium complex (n=14), the sensitivity of RGM was 93% compared with 79% for AFB culture (p=0.62). Mycobacterium abscessus complex (n=4) and Mycobacterium chelonae (n=24) were recovered on RGM medium, but neither of these was recovered using AFB culture. Conclusions: Culture on RGM medium offers a very simple and highly sensitive method for detection of NTM from individuals with BR, without any need for sample decontamination or instrumentation. Culture on RGM medium can be incorporated alongside culture for other bacterial pathogens allowing regular screening for NTM for every sample submitted to the laboratory, for individuals with BR. The clinical significance of the large number of additional isolates of NTM recovered using RGM medium needs to be established by ongoing long term studies.